EXTENSION ADMINISTRATION PERFORMANCE UNDER QUALITY STANDARDS FROM THE PERSPECTIVE OF THE WORKING STAFF IN AGRICULTURAL EXTENSION AND VEGETABLES FARMERS OF CENTRAL GOVERNORATES IN IRAQ - عبد الرزاق اشواق; جوحي احمد سعدون (Journal of Economics and Administrative Sciences, 2014)
This research aims to identify the level of extension administration performance under comprehensive quality standards from the perspective of the working staff in agricultural extension at the level of the general extension body and agricultural directorates and agricultural division.this was to identify the extension administration performance under comprehensive quality standards from the perspective of vegetables growers , random sample was selected from the central region governorates Baghdad , Diyala , Babel , karbala and Al-Najaf , a random sample from the workers in the general body numbered 56 employee , sample of staff working in agricultural extension was selected at the level of agricultural directorates in proportional , stratifies , and preview manner numbered 41 employee , sample of staff working in agricultural extension was selected at the level of agricultural extension was selected at the level of agricultural divisions in proportional , stratifies , and preview manner numbered 100 farmer , so the research found that the level of extension administration performance in its different levels from the viewpoint of staff working in agricultural extension was moderate , that the level of extension administration performance in its different levels from the viewpoint of farmer vegetables growers was weak special at agricultural division , , the researcher recommends the need to create an independent administrative body concerns with the responsibility of quality assurance in the extension administrative work and works on the evaluation of extension administration performance in its different levels according to comprehensive quality administration standards to suit its work and geographical environment of iraq periodically